Bio-Inspired routing control in a "Smart-Cross-Dock": Simulation Approach. Issue 1 (July 2017) - Tetouani, Samir; Chouar, Abdessamad; Soulhi, Aziz; Alami, Jamila El
Abstract: Flocking is a fascinating collective behaviour exhibited by many different insects or animals including ants, bees, birds and fish. As understood by biologists, the overall flocking behaviour emerges from relatively simple local control rules by which each smart-pallet adjusts its own trajectory based on those of its closest neighbours. We use, in this article, "flocking principle" to simulate a routing algorithm based on a multi agent system in a Smart-Cross-Dock. We use the level of visibility to avoid the obstacles and the congestions in the cross-dock platform. We specify a number of methodologies for placing the influencing smart-pallet into the flock, and comparing them via detailed experimental results.